2016
DOI: 10.1002/adsc.201600615
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Hydrazino Amino Acyclic Carbenes of Gold(I), Platinum(II), Palladium(II) and Rhodium(III)

Abstract: The nucleophilic addition of protected and substituted hydrazine derivatives to isonitrile complexes of gold(I), platinum(II), palladium(II) and rhodium(III) provides the corresponding hydrazino amino acyclic carbene complexes. These are characterized by their spectroscopic data, four different X‐ray single crystal structure analyses and their catalytic activity in the gold(I)‐catalyzed cycloisomerization of N‐propargylcarboxamides to alkylideneoxazolines is investigated.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…Previous studies on this cycloisomerization reaction have shown 95 % yield in 12 hours using 5 mol % of AuCl 3 or 79 % after 36 hours, employing a lower catalyst loading of a phosphine‐based complex (1.0 mol % (Ph 3 P)AuNTf 2 ) . Recently, some examples of HAAC (Hydrazino amino acyclic carbene) complexes were developed in our group, that gave up to 100 % yield, but at the expense of a prolonged reaction time (2 days) …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on this cycloisomerization reaction have shown 95 % yield in 12 hours using 5 mol % of AuCl 3 or 79 % after 36 hours, employing a lower catalyst loading of a phosphine‐based complex (1.0 mol % (Ph 3 P)AuNTf 2 ) . Recently, some examples of HAAC (Hydrazino amino acyclic carbene) complexes were developed in our group, that gave up to 100 % yield, but at the expense of a prolonged reaction time (2 days) …”
Section: Resultsmentioning
confidence: 99%
“…This reaction has previously been used to benchmark catalyst activity and the effectiveness of added activators in homogenous gold catalysis. [31][32][33][34] The reaction was performed with 2 mol % of chloro(triphenylphosphine) gold and an equimolar amount of the halide abstracting agent in deuterated chloroform as solvent.…”
mentioning
confidence: 99%
“…The presence of only one C≡N peak indicates on the presence in the structure of one unreacted isocyanide ligand. The longwave shift of the C≡N peak on the transition PdCl 2 (CNR) 2 → PdCl 2 (ADC)(CNR) accords with higher σ-donating ability of the ADC ligand compared to isocyanide [53][54][55][56][57].…”
Section: Resultsmentioning
confidence: 81%